The Cao-Xiang-Wei-Kang formula attenuates the progression of experimental colitis by restoring the homeostasis of the microbiome and suppressing inflammation - Yu, Wei; Li, Qi; Shao, Changlei; Zhang, Yijia; Kang, Cai; Zheng, Yang; Liu, Xihao; Liu, Xincheng; Yan, Jing (Frontiers in Pharmacology, 2022)
Inflammatory bowel disease (IBD) is pathologically characterized by an immune response accommodative insufficiency and dysbiosis accompanied by persistent epithelial barrier dysfunction. The Cao-Xiang-Wei-Kang (CW) formula has been utilized to treat gastrointestinal disorders in the clinic. The present study was designed to delineate the pharmacological mechanisms of this formula from different aspects of the etiology of ulcerative colitis (UC), a major subtype of IBD. Dextran sodium sulfate (DSS) was given to mice for a week at a concentration of 2%, and the CW solution was administered for 3 weeks. 16S rRNA gene sequencing and untargeted metabolomics were conducted to examine the changes in the microbiome profile, and biochemical experiments were performed to confirm the therapeutic functions predicted by system pharmacology analysis. The CW treatment hampered DSS-induced experimental colitis progression, and the targets were enriched in inflammation, infection, and tumorigenesis, which was corroborated by suppressed caspase 3 (Casp3) and interleukin-1b (IL-1b) and increased cleaved caspase 3 expression and casp-3 activity in the colon samples from colitis mice subjected to the CW therapy. Moreover, the CW therapy rescued the decreased richness and diversity, suppressed the potentially pathogenic phenotype of the gut microorganisms, and reversed the altered linoleic acid metabolism and cytochrome P450 activity in murine colitis models. In our in vitro experiments, the CW administration increased the alternative activation of macrophages (Mφs) and inhibited the tumor necrosis factor-α (TNFα)-induced reactive oxygen species (ROS) level and subsequent death in intestinal organoids (IOs). We propose that the CW formula alleviates the progression of murine colitis by suppressing inflammation, promoting mucosal healing, and re-establishing a microbiome profile that favors re-epithelization.